PSGpower: A MATLAB toolbox for analyzing sleep EEG data - Ahren B. Fitzroy; Rebecca M.C. Spencer (SoftwareX)
Sleep science has seen a surge in discoveries fueled by enhanced data processing approaches to sleep physiology recordings. PSGpower is a MATLAB toolbox designed to make these processing steps more efficient and standardized. PSGpower imports sleep polysomnography data recorded using legacy and modern acquisition systems, and sleep-staged using a variety of software packages, for processing in a number of microstructure analysis workflows. Workflows include existing algorithms from EEGLAB and FieldTrip and custom algorithms. PSGpower is extensible, and new workflows can be added that take advantage of the common data importing, sleep stage marking, and preprocessing code.